The genus Hylaeus Fabricius in Mongolia, an updated species inventory (Hymenoptera: Apoidea, Colletidae) - Dathe, Holger H.; Proshchalykin, Maxim Yu. (Zootaxa, 2016)
Since the last inventory of Hylaeus species of Mongolia (Dathe 1986a) extensive new collections have been evaluated. An updated checklist of 38 species of Hylaeus so far known from Mongolia is provided, with comments on their biogeographical assignment. Two new species, Hylaeus (Hylaeus) kozlovi sp. n. and Hylaeus (Hylaeus) mellon sp. n., are described. Hylaeus albitarsis Morawitz, 1887 (= H. fuliginosus Warncke, 1972) has been ascertained as a synonym of Hylaeus (Hylaeus) pusillus (Warncke, 1972). The following nine known species are newly recorded from Mongolia: H. (Dentigera) pallidicornis Morawitz, 1876, H. (Hylaeus) aborigensis Dathe, 1994, H. (Hylaeus) angustatus (Schenck, 1861), H. (Hylaeus) fedtschenkoi (Cockerell, 1906), H. (Hylaeus) oblitus (Warncke, 1972), H. (Hylaeus) vulgaris Morawitz, 1876, H. (Lambdopsis) pfankuchi (Alfken, 1919), H. (Nesoprosopis) pectoralis Förster, 1871, H. (Patagiata) nigrocuneatus Cockerell, 1924.